Ինքնաճանաչողության միֆական միջավայրի ստեղծումը1990-ականների սկզբի մամուլում - Սարգսյան, Զարուհի
Мифы и воспоминания о прошлом продолжают играть важную роль в формировании национальной идентичности в эпоху глобализации. Уже в начале Карабахского движения наблюдалось возвращение к национальным корням: уделялось больше внимания важности исторического прошлого и мифического прототипа, роли веры в борьбе нации за выживание. Эти факторы не просто решали проблему отличия <<своего>> и <<чужого>>, но и пытались сделать более ровным будущий путь развития. Myths and recollections of the past are still playing a vital role in molding national identity in the age of globalization. At the beginning of the Karabakh movement we could witness reversion to national roots. Right at this time historical past, mythical prototypes and the role of religion in the strife for survival were paid due attention. These factors were considered to be not only the ones to resolve the difference between the concepts of “own” and “alien”, but they were also thought to be attempts to lay foundations for a smoother way for future prospects.
Keywords: Պատմություն; Հայ մամուլ; Ազգայնականություն